2023
DOI: 10.1111/ejh.13959
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, prognostic factors, and survival outcomes in patients with blastic plasmacytoid dendritic cell neoplasm: A retrospective study in the Surveillance, Epidemiology, and End Results database

Abstract: There are few large‐scale epidemiological and prognostic studies on blastic plasmacytoid dendritic cell neoplasm (BPDCN) due to its rarity. We used the Surveillance, Epidemiology, and End Results database to investigate the incidence, clinical characteristics, prognostic factors, and survival trends of BPDCN. The age‐adjusted incidence of BPDCN had a bimodal pattern with peaks in those under 20 and 60 years and older. Of 697 patients, the median age at diagnosis was 31 years. The most common primary sites were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In a retrospective study, age > 60 years at diagnosis, abnormal karyotype, and terminal deoxynucleotidyl transferase negativity were suggested to be associated with worse treatment responses [ 47 ]. In another study, multivariate Cox regression analysis revealed that advanced age, male gender, and BPDCN occurring as the first malignancy were independent prognostic factors for overall survival [ 48 ]. Yin et al suggested that older age, multiple mutations, and mutations in the DNA methylation pathway were poor prognostic factors for BPDCN [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, age > 60 years at diagnosis, abnormal karyotype, and terminal deoxynucleotidyl transferase negativity were suggested to be associated with worse treatment responses [ 47 ]. In another study, multivariate Cox regression analysis revealed that advanced age, male gender, and BPDCN occurring as the first malignancy were independent prognostic factors for overall survival [ 48 ]. Yin et al suggested that older age, multiple mutations, and mutations in the DNA methylation pathway were poor prognostic factors for BPDCN [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…pDCs are largely responsible for viral defense, as upon maturation, these cells are responsible for secreting cytokines such as type I interferon (IFN), interleukin-6, interleukin-8, and tumor necrosis alpha. This allows for the activation of T-cells, macrophages, and NK cells [1]. Initially, BPDCN was thought to be an NK cell malignancy due to presence of CD4+ and CD56+ cells when immunotyping of cells was conducted.…”
Section: Pathophysiology Of Cns Involvement In Bpdcnmentioning
confidence: 99%
“…Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare and aggressive hematologic malignancy primarily afflicting middle-aged to older men and has poor survival outcomes [1,2]. Although the median age of diagnosis is around 65 years of age, BPDCN has also been seen in younger populations, including children in a bimodal distribution pattern.…”
Section: Introductionmentioning
confidence: 99%
“…With a reported incidence of 0.04 cases per 100.000 in the US, it represents less than 1% of all hematologic malignancies. The median age of onset of the adult variant is around 70 years and men are more frequently affected ( 2 ). The typical presentation consists of characteristic skin lesions as well as affection as leukemia or of lymph nodes, liver, spleen and, less frequently, other extramedullary sites such as the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%